High Oxidizing Stability and Ion Selectivity of Hybrid Polymer Electrolyte Membrane for Improving Electrochemical Performance in Vanadium Redox Flow Battery. Issue 10 (1st January 2018) - Thong, Pham Tan; Sadhasivam, T.; Lim, Hankwon; Jin, Chang-Soo; Ryi, Shin-Kun; Park, WonShik; Kim, Hee Tak; Roh, Sung-Hee; Jung, Ho-Young
Abstract : The research work examines effects of organic-inorganic hybrid membrane made of low-cost sulfonated poly(2, 6-dimethyl-1, 4-phenylene oxide) (SPPO) and graphene oxide (GO) to improve the membrane properties for application in vanadium redox flow battery (VRFB). SPPO membrane alone is economical but undesirable for VRFB operation because it is significantly vulnerable to degradation in vanadium electrolyte. For this reason, the inorganic GO is introduced into the SPPO polymer matrix, thus beneficial effects are acquired specifically that the hybrid SPPO-GO membrane shows enhanced chemical-physical properties, especially higher ion selectivity is obtained for 2 wt% GO incorporated into SPPO, the greater than pure SPPO and Nafion 212 membrane. Furthermore, vanadium permeability is lowered for composite membrane incorporated with GO. Importantly, the hybrid membrane shows increased oxidizing stability in comparison to the SPPO membrane alone. Accordingly, the hybrid SPPO-GO membrane obtains higher efficiencies than pure SPPO membrane in VRFB cell test. Therefore, the results of this work can reveal promising consideration on the use of economical polymer membrane for further development in VRFB application.